Wanprestasi Dalam Perjanjian Kerja Sama dan Penunjukkan Pekerjaan Rumah Tahan Gempa: (Analisis Putusan Pengadilan Negeri Mataram Nomor 194/Pdt.G/2020/PN Mtr) - Ghennia Dzinur Arninda; H. Zaenal Arifin Dilaga (Private Law, 2022)
The purpose of this study is to find out the basis of the judge's consideration in deciding the case of default in the cooperation agreement and job appointment of the earthquake-resistant house and its legal consequences as stated in the Mataram District Court Decision No. 194 / Pdt.G / 2020 / PN Mtr. This is a normative legal research. This research finds out that the judge's consideration in deciding the case of default as stated in the Mataram District Court Decision No. 194 / Pdt.G / 2020 / PN Mtr is based on the legal expert opinion regarding the default, the propositions and arguments of the lawsuit and also the evidence from the plaintiff. As for the legal consequence of the breach of such agreements results in the Defendant pays the losses suffered by the plaintiff and the costs of the case.